2005
DOI: 10.1038/nrm1547
|View full text |Cite
|
Sign up to set email alerts
|

Function and regulation of cullin–RING ubiquitin ligases

Abstract: Multisubunit UBIQUITIN LIGASES (E3s) that are assembled on a CULLIN scaffold were first reported seven years ago 1,2. The discovery of the archetypical cullin-RING ubiquitin ligase-SCF Cdc4-benefited from a strong foundation of genetic studies on cell division in Saccharomyces cerevisiae and Caenorhabditis elegans. The model established by SCF can now be extended to a superfamily of CULLIN-RING LIGASES (CRLS) that are found throughout eukaryotes. Together, these enzymes regulate a dazzling array of cellular an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
2,087
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,936 publications
(2,115 citation statements)
references
References 139 publications
23
2,087
1
4
Order By: Relevance
“…The increase of CSN5 isopeptidase activity might be explained by a conformational change induced by cleaving off 23 amino acids of CSN6. Since CSN-mediated deneddylation prevents CRL complex assembly [2,4,43], it is conceivable to assume that the elevation of this activity is another strategy to knockout CRLs during apoptosis. In fact, it has been shown that the typical Cul1-CRL substrate, p27 Kip [44], is accumulated in tumor cells after treatment with etoposide [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of CSN5 isopeptidase activity might be explained by a conformational change induced by cleaving off 23 amino acids of CSN6. Since CSN-mediated deneddylation prevents CRL complex assembly [2,4,43], it is conceivable to assume that the elevation of this activity is another strategy to knockout CRLs during apoptosis. In fact, it has been shown that the typical Cul1-CRL substrate, p27 Kip [44], is accumulated in tumor cells after treatment with etoposide [45].…”
Section: Discussionmentioning
confidence: 99%
“…The CSN interacts with components of the ubiquitin (Ub) proteasome system (UPS) known as cullin-RING Ub ligases (CRLs) [2]. These enzyme complexes select proteins for ubiquitination and are responsible for substrate specificity of the UPS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDB1 is unrelated to SKP1 and ELOC, but also associates with the N-terminus of the cullin. For each receptor family, between 20 and 100 specific receptor proteins have been identified [21,22]. In addition, PARC/CUL9 has been shown to bind to RBX1 and to be neddylated, but it does not associate with SKP1 or F-box proteins [101], and its molecular functions and adaptors remain to be identified.…”
Section: Mechanism Of Cullin Neddylationmentioning
confidence: 99%
“…As expanded on below, however, the available data indicate that the CRL is unlikely to be in this basal state for a substantial amount of time and, in principle, will probably populate a wide range of architectures during its lifetime. Relevant events that modify the CRL architecture include: activation through the process of neddylation; association of the active neddylated form with the COP9 signalosome (CSN) complex, a multisubunit deneddylase that can sterically block substrate access, catalyse cullin deneddylation, and remain bound to the CRL; loss of SR through proteolytic degradation; and SR exchange via a CAND1-driven mechanism [21,[34][35][36][37][38][40][41][42][43]. A confounding factor to understanding this regulation is that in cells these different events are generally not synchronized for CRLs en masse, or for individual CRL SR complexes.…”
mentioning
confidence: 99%